2007
DOI: 10.1111/j.1365-2222.2007.02870.x
|View full text |Cite
|
Sign up to set email alerts
|

Drug allergy claims in children: from self‐reporting to confirmed diagnosis

Abstract: ADRs are frequently reported in children, and many children are classified as having a DAll. After complete evaluation, only a few of these reactions can be attributed to DHs and DAll. Most of the patients (94% in this study) could actually tolerate the initially suspected drug.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(51 citation statements)
references
References 41 publications
1
48
1
1
Order By: Relevance
“…Previous Portuguese population studies on the prevalence of drug HS found that 8% of adults and 6% of children self-reported allergy to at least one drug, with NSAIDs being the second-most suspected [14,15]. In a recent Portuguese study on drug-induced anaphylaxis, NSAIDs were the most frequent culprits [16].…”
Section: Introductionmentioning
confidence: 99%
“…Previous Portuguese population studies on the prevalence of drug HS found that 8% of adults and 6% of children self-reported allergy to at least one drug, with NSAIDs being the second-most suspected [14,15]. In a recent Portuguese study on drug-induced anaphylaxis, NSAIDs were the most frequent culprits [16].…”
Section: Introductionmentioning
confidence: 99%
“…The evidence review found that the prevalence of true penicillin allergy is much less common than perceived allergy and that re-sensitisation to β-lactam drugs was infrequent 46. A detailed history is required for an accurate diagnosis of a drug-induced reaction and skin prick tests should not be used to screen for drug allergy in the absence of a clinical history compatible with IgE-mediated drug allergy 7.…”
Section: Resultsmentioning
confidence: 99%
“…Although approximately 8% of Americans are labelled as being allergic to penicillin [7], a meta-analysis by Harandian et al [8] found that just 3% of patients with penicillin allergy in their medical records had a confirmed diagnosis of immediate reactions by skin or drug provocation tests. The difference appears to be even more striking in the paediatric population, in whom penicillin allergy diagnoses based solely on clinical history are more common [1, 9, 10]. According to the above-mentioned meta-analysis, the frequency of confirmed immediate reactions to penicillin is less than 2% in children [8].…”
Section: Introductionmentioning
confidence: 99%
“…According to the above-mentioned meta-analysis, the frequency of confirmed immediate reactions to penicillin is less than 2% in children [8]. Overdiagnosis of penicillin allergy has also been reported for non-immediate reactions, as children with infectious rashes are frequently misdiagnosed with allergic maculopapular exanthemas [1, 9]. …”
Section: Introductionmentioning
confidence: 99%